1994
DOI: 10.1104/pp.106.4.1533
|View full text |Cite
|
Sign up to set email alerts
|

Floral Scent Production in Clarkia (Onagraceae) (I. Localization and Developmental Modulation of Monoterpene Emission and Linalool Synthase Activity)

Abstract: The flowers of many plants emit volatile compounds as a means of attracting pollinators. We have previously shown that the strong, sweet fragrance of CIarkia breweri (Onagraceae), an annual plant native to California, consists of approximately 8 to 12 volatile compounds-three monoterpenes and nine benzoate derivatives (R.A. Raguso and E. Pichersky [1994] Plant Syst Evol [in press]). Here we report that the monoterpene alcohol linalool is synthesized and emitted mostly by petals but to a lesser extent also by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
143
1
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(159 citation statements)
references
References 19 publications
10
143
1
5
Order By: Relevance
“…The close correspondence between in vitro enzyme activity and the rate of monoterpene biosynthesis measured in vivo suggests that monoterpene formation in peppermint oil gland cells is tightly controlled by the levels of biosynthetic enzymes. Similar correlations have been noted for the formation of a variety of isoprenoids during flower (Pichersky et al, 1994), leaf (Croteau et al, 1981), and seedling (Green and Baisted, 1972) development, and after induction by pathogens (Dudley et al, 1986;Hanley et al, 1992), but this is the first time that a related array of isoprenoid biosynthetic enzymes has been investigated in a single specialized cell type.…”
Section: Developmental Regulation Of Monoterpene Biosynthetic Activitymentioning
confidence: 67%
“…The close correspondence between in vitro enzyme activity and the rate of monoterpene biosynthesis measured in vivo suggests that monoterpene formation in peppermint oil gland cells is tightly controlled by the levels of biosynthetic enzymes. Similar correlations have been noted for the formation of a variety of isoprenoids during flower (Pichersky et al, 1994), leaf (Croteau et al, 1981), and seedling (Green and Baisted, 1972) development, and after induction by pathogens (Dudley et al, 1986;Hanley et al, 1992), but this is the first time that a related array of isoprenoid biosynthetic enzymes has been investigated in a single specialized cell type.…”
Section: Developmental Regulation Of Monoterpene Biosynthetic Activitymentioning
confidence: 67%
“…These results are very similar to those obtained for LIS, an enzyme that produces linalool, another floral scent compound in C. breweri. We observed strong positive correlation between levels of LIS enzyme activity, protein, and mRNA at the site of synthesis and emission of linalool in the flower (Pichersky et al, 1994;Dudareva et al, 1996).…”
Section: Biosynthesis Of Methyleugenol and Isomethyleugenol And The Ementioning
confidence: 70%
“…The strong, sweet fragrance of C. breweri consists of 8 to 12 different volatiles that fall into two groups: monoterpenoids and phenylpropanoids-benzenoids (Raguso and Pichersky, 1995). We have shown that linalool, an acyclic monoterpene, is synthesized in C. breweri petals and other floral tissues in a reaction catalyzed by LIS (Pichersky et al, 1994(Pichersky et al, , 1995, and that the enzyme activity is regulated at a pretranslational level (Dudareva et al, 1996). A closely related species, Clarkia concinna (from which C. breweri is believed to have evolved [Raguso and Pichersky, 1995]), also possesses the gene encoding LIS, but the expression of this gene in this nonscented species is limited to the stigma, and the level of expression is much lower than in the stigma of C. breweri.…”
mentioning
confidence: 99%
“…6A). Day 2 of anthesis is the day in which the stigma opens up and becomes receptive, a process that involves rapid cell expansion and consequently a reduction in protein content per cell (Pichersky et al, 1994). However, even when BEBT activity levels and BEBT protein levels are plotted after normalization to protein content (data not shown), a substantial drop of 50% in both is still observed from d 1 to 2.…”
Section: Discussion Bebt a Bahd-type Acyltransferase Is Responsiblementioning
confidence: 94%